Neurological improvement predicts clinical outcome after acute basilar artery stroke thrombectomy. (17th September 2020) - Guenego, A.; Bourcier, R.; Guillen, M.; Weisenburger‐Lile, D.; Lapergue, B.; Gory, B.; Richard, S.; Ducroux, C.; Piotin, M.; Blanc, R.; Labreuche, J.; Lucas, L.; et al.
Abstract : Background and purpose: Mechanical thrombectomy (MT) is the standard of care for patients with anterior circulation large vessel occlusion. Early neurological improvement (ENI), defined as a reduction of ≥ 8 on the National Institutes of Health Stroke Scale (NIHSS) compared with baseline score, or an NIHSS score of 0 or 1 at 24 h after MT, is a strong predictor of 3‐month favorable outcome in such patients. The impact of ENI after MT in stroke patients with basilar artery occlusion (BAO) on 3‐month outcome is not clear. We aimed to study the effects of ENI in patients with BAO. Methods: We performed a retrospective analysis of a multicenter prospective cohort of all consecutive stroke patients with BAO who underwent MT. We compared clinical outcomes between BAO patient groups according to ENI status. Multivariate analyses were performed to determine the impact of ENI on favorable 90‐day outcome (modified Rankin scale score 0–3) and to report factors contributing to ENI. Results: A total of 237 patients were included. ENI was observed in 70 patients (30%). Outcomes were significantly better in ENI‐positive patients, with 84% achieving favorable outcome (mRS score 0–3) at 3 months versus 30% for ENI‐negative patients ( P < 0.0001). In multivariate analysis, ENI was an independent predictive factor associated with higher rates of favorable outcome odds ratio (OR) 18.12 [95% confidence interval (CI) 3.95–83.10]; P = 0.0001. Higher number of passes [OR 0.62 (95% CI 0.43–0.89); P = 0.010] and need for stenting [OR 0.27 (95% CI 0.07–0.95); P = 0.041] were negatively associated with ENI. Conclusion: Early neurological improvement on day 1 following MT for BAO is a strong independent predictor of a favorable 3‐month clinical outcome. Abstract : Early neurological improvement on day 1 following thrombectomy for basilar artery occlusion is a strong independent predictor of a favorable 3‐month clinical outcome.